2020
DOI: 10.1590/2177-6709.25.4.016-022.oin
|View full text |Cite
|
Sign up to set email alerts
|

Negligible tooth resorptions after anterior open bite treatment using skeletal anchorage with miniplates

Abstract: Introduction: When miniplates are used as anchoring for orthodontic mechanics for anterior open bite correction by retraction of anterior teeth and posterior teeth intrusion and retraction, orthodontically induced inflammatory external apical root resorption is clinically negligible. Methods: A homogeneous sample of 32 patients was used, and the roots of the teeth were compared on CT scans performed before and after orthodontic treatment. Results: The observed root resorption was minimal, and this can be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Additionally, two mandibular miniplates, also in the shape of a “T”, were placed on the posteroinferior region of the mandibular buccal cortex on both the right and left sides. Alignment and leveling were achieved with progressive increase in wire size including 0.016″ × 0.016″ Neo Sentalloy ® 80 g Dentsply GAC International ® (Iceland, NY, USA), 0.016″ × 0.016″ Titanol low force ® 80 g Forestadent® (Pforzheim, Germany), 0.016″ × 0.022″ Titanol low force® 120 g Forestadent ® (Pforzheim, Germany), 0.016″ × 0.016″ Blue Elgiloy ® Rocky Mountain Orthodontics ® (Denver, CO, USA) e 0.016″ × 0.022″ Blue Elgiloy ® Rocky Mountain Orthodontics ® (Denver, CO, USA) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, two mandibular miniplates, also in the shape of a “T”, were placed on the posteroinferior region of the mandibular buccal cortex on both the right and left sides. Alignment and leveling were achieved with progressive increase in wire size including 0.016″ × 0.016″ Neo Sentalloy ® 80 g Dentsply GAC International ® (Iceland, NY, USA), 0.016″ × 0.016″ Titanol low force ® 80 g Forestadent® (Pforzheim, Germany), 0.016″ × 0.022″ Titanol low force® 120 g Forestadent ® (Pforzheim, Germany), 0.016″ × 0.016″ Blue Elgiloy ® Rocky Mountain Orthodontics ® (Denver, CO, USA) e 0.016″ × 0.022″ Blue Elgiloy ® Rocky Mountain Orthodontics ® (Denver, CO, USA) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the induced tooth-bone movement with enhanced anchorage, the applied force is distributed more uniformly across the bone and tooth structures, justifying why tooth resorptions are less frequent and intense in orthodontic treatments with miniplates than those observed in conventional treatments. [8][9][10][11][12]…”
Section: Applied Forces: Distribution X Intensitymentioning
confidence: 99%
“…This reduces the possibility of death of cementoblasts along the root, and reduces the chance of root resorptions. 16 Pure intrusive forces in Orthodontics exist only experimentally and, when resorptions occur at the apexes and bifurcations of these teeth, they are detectable only under a microscope, as they cannot be diagnosed by imaging exams. [3][4][5][6] Studies have revealed that when intrusive forces are eliminated, neighboring tissues quickly repair the resorbed areas.…”
Section: Tooth Resorption and Intrusive Mechanicsmentioning
confidence: 99%
“…1 The intrusive effect in so-called intrusive mechanics may be the result of alveolar remodeling induced by inclination forces and changes in bone volume resulting from subperiosteal bone formation in the external part of the alveolar process 1 , 5 , 8 The more homogeneous distribution of forces with absolute anchorage on miniplates explains the insignificant level of root resorption. 16 …”
Section: Final Considerationsmentioning
confidence: 99%
See 1 more Smart Citation